2016
DOI: 10.1007/s40519-016-0328-y
|View full text |Cite|
|
Sign up to set email alerts
|

Shame proneness and eating disorders: a comparison between clinical and non-clinical samples

Abstract: Shame proneness can be an important component for the development and the maintenance of ED due to a strong correlation not only with ED symptoms but also with psychological aspects of this disease, in both clinical and non-clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 28 publications
(46 reference statements)
0
8
0
1
Order By: Relevance
“…Cesare et al . () found no significant association between shame proneness and ED symptoms in either AN or BN subgroups, though a moderately sized but non‐significant correlation between drive for thinness and shame proneness was reported in the AN group ( r = .33).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Cesare et al . () found no significant association between shame proneness and ED symptoms in either AN or BN subgroups, though a moderately sized but non‐significant correlation between drive for thinness and shame proneness was reported in the AN group ( r = .33).…”
Section: Resultsmentioning
confidence: 89%
“…A summary of results and effect sizes is reported in Table for studies investigating shame using group comparison designs. Individuals with AN or BN presentations reported greater shame compared to non‐clinical control groups, with typically large effect sizes (Cardi, Di Matteo, Gilbert, & Treasure, ; Cesare et al ., ; Doran & Lewis, ; Ferreira, Pinto‐Gouveia, & Duarte, ; Kollei, Brunhoeber, Rauh, de Zwaan, & Martin, ; Overton, Selway, Strongman, & Houston, ; Swan & Andrews, ). These differences were apparent across multiple forms of shame (shame related to body/physical appearance; shame related to personal attributes/character; shame related to behaviour; external shame; shame related to eating) with the largest differences apparent for eating‐related shame ( k = 1; d = 2.77; ΔPOMS = 70%) and the smallest differences apparent for shame proneness ( k = 1; d = 0.88; ΔPOMS = 15%).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies examined internal shame, which describes an inwardly focussed sense of inadequacy, inferiority and badness compared to others. Four studies used group comparison design, three of which identified greater levels of internal shame in samples with BED or subthreshold BED than in healthy controls ( d = 0.78 to 1.36; Cesare et al, 2016; Masheb et al, 1999; Sanftner & Crowther, 1998). The study by Sanftner and Crowther (1998) found that university students who engaged in subthreshold binge eating experienced higher levels of and greater daily fluctuations in internal shame compared to healthy controls, although levels of internal shame did not increase across the 9 h leading up to binge eating episodes.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics also typify individuals with depression and disordered eating (e.g., Fairburn, Cooper, & Shafran, 2003; Jacobi, Paul, de Zwaan, Nutzinger, & Dahme, 2004; Orth, Berking, & Burkhardt, 2006). Previous research shows that SP and SC are both strongly associated with depression and disordered eating (Cesare et al, 2016; Tangney & Dearing, 2002; Dunkley & Grilo, 2007). Surprisingly, SP and SC have never been simultaneously examined in relation to these psychopathologies, making it difficult to distinguish their unique contributions to the comorbidity between these outcomes.…”
Section: Introductionmentioning
confidence: 99%